1992
DOI: 10.1089/thy.1992.2.21
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Variant of Transthyretin (Prealbumin), Thr119to Met, Associated with Increased Thyroxine Binding

Abstract: A group of patients with prealbumin associated hyperthyroxinemia possess a common single base substitution in the fourth exon of their transthyretin gene. This cytosine to thymine substitution occurs in the codon for residue 119 and results in the predicted replacement of a threonine residue with a methionine at this position. A new NcoI restriction endonuclease cleavage site is created by the point mutation and can be detected by a rapid and simple assay based on the polymerase chain reaction. This variant tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…TTR A109V has a similar thyroid phenotype and binding affinity for T 4 (25). Subjects with TTR T119M (26) have normal or slightly elevated serum T 4 and rT 3 concentrations. The mechanism underlying the slight increase in serumT 4 has been a subject of debate.…”
Section: Transthyretin (Ttr)mentioning
confidence: 99%
See 1 more Smart Citation
“…TTR A109V has a similar thyroid phenotype and binding affinity for T 4 (25). Subjects with TTR T119M (26) have normal or slightly elevated serum T 4 and rT 3 concentrations. The mechanism underlying the slight increase in serumT 4 has been a subject of debate.…”
Section: Transthyretin (Ttr)mentioning
confidence: 99%
“…On the contrary, Almeida et al (28) showed increased T 4 -binding affinity. Interestingly, the presence of hyperthyroxinemia in these cases is transient and brought about by non-thyroidal illness, either by increasing the proportion of heterotetramers or through an unexpected effect of non-thyroidal illness on T 4 binding to the mutant TTR (26). Finally, TTR G6S, with a frequency of 12% (29), identified in a family with euthyroid hyperthyroxinemia and a 4-fold higher T 4 -binding affinity than normal TTR (30), was shown to have normal T 4 -binding in another study.…”
Section: Transthyretin (Ttr)mentioning
confidence: 99%
“…In 1991, in the initial description of the Thr119Met variant by Harrison et al [51], no increase in transthyretin binding of thyroxine was found after isoelectric focussing. In 1992, Scrimshaw et al [52] examined the Thr119Met variant and found increased precipitation of both 125 I-thyroxine and 125 I-tri-iodothyronine by anti-transthyretin antibodies and postulated that the substitution resulted in an increased affinity of the Thr119Met transthyretin for thyroxine. However, after the publication of the results of the research group of Pedro Costa and Maria Saraiva described above, in 1994, the group set out to determine definitively whether the increase in the amount of thyroxine carried by the Thr119Met transthyretin was due to a change in affinity for thyroxine or to a change in thyroxine-binding capacity [53].…”
Section: Further Studies On Thyroxine Bindingmentioning
confidence: 99%
“…Of these, Thr119Met (⌬m ϭ 29.992 Da) agrees most closely with the observed mass difference (versus ⌬m ϭ 30.011 Da for the other possible mutation; Ala109Thr). The Thr119Met variant has been characterized previously and is referred to as TTR "Chicago" variant, which is found to be nonamyloidogenic (42,43).…”
Section: Ttr Mappingmentioning
confidence: 99%